A New Scheme For Reduction Of Peak-To-A Verage Power Ratio In Orthogonal Frequency Division Multiplexing - Melad, Ahmed Mustafa H (2003)
Orthogonal Frequency Division Multiplexing (OFDM) is an attractive modulation method for channels with a non-flat frequency response. as it saves the need for complex equalizers. However. its main disadvantage is the high peak-to-average power ratio (PAPR) of the output signal. which may take values within a range that is proportional to the number of carriers in the system. As a result, a linear behavior of the system over a large dynamic range is needed and therefore the efficiency of the output amplifier is reduced. Many methods have been proposed to reduce the PAPR of the OFDM signal. among them a clipping technique which has been focused and investigated.OFDM signal, among them a clipping technique which has been focused and investigated. This thesis proposes a new scheme to reduce the PAPR. We name it Off technique. Further the effects of clipping scheme as well as the new scheme on the OFDM system performance in terms of Bit Error Rate (BER) and PAPR reduction is investigated. The results obtained indicate that both parameters, i .e. the reduction in PAPR and BER of this scheme were worse than those of the Clipping Scheme. In conclusion, results indicate that Off Technique does not offer a better solution to PAPR reduction in the OFDM system.